An atypical case of optic disk drusen with nerve fiber layer thickening - Turgut, Burak; Kaya, Mehmet Kaan; Demir, Tamer (Dove Medical Press Ltd, 2010)
We report an atypical case of optic disk drusen (ODD). A 12-year-old girl complained of blurred vision in both eyes. However, visual acuities in both eyes were 20/ 20. Fundus examination revealed blurring of the optic disk margins and elevation of the optic disk in both eyes. Initially it was considered that the diagnosis would be papilledema. However, neurologic examination revealed no pathology which would cause the visual field defect and disk elevation. Optical coherence tomography (OCT) scans showed hyperreflectance lesions on the disk and shadowing areas beneath the optic nerve head in both eyes. Orbital ultrasound and orbital and cranial tomography revealed protuberances with hyperechogenicity and calcification in both eyes. It was considered that these findings were consistent with ODD. Repeated visual field tests showed constricted peripheral field loss in both eyes. Using OCT software, peripapillary nerve fiber layer thickening in both eyes corresponded to visual field defects in the superior and inferior quadrants, in which drusen was detected. Despite the extensive literature, in cases of ODD with blurred margins, elevated disks, and visual field defects, the peripapillary nerve fiber layer may be increased due to nerve layer infarct in the area which has calcification.
Keywords: optic disk drusen; pseudopapilledema; retinal nerve fiber; infarct; thickening